DAMPAK PANDEMI COVID-19 TERHADAP PENDAPATAN PETANI LEGEN DI DUSUN SEBERO DESA DALEGAN PANCENG GRESIK - Nur Sa’idaturrohmah; Lailatul Khofifah (Al-Musthofa: Journal of Sharia Economics, 2021)
The agricultural sector is one of the sectors most affected by the Covid 19 pandemic. The spread of the disease is very fast, it is not yet known when it will end. From 2019 to 2021 it's not just over with this pandemic problem. What's more, legen farmer have lost up to 70% of their income. The purpose of this study was to find out the impact of the Covid-19 pandemic on the income level of legen farmers in Sebero hamlet before and during the pandemic.